Environment-friendly chemical synthesis of calcium hydroxide nano-powders from waste perna viridis shells for the adsorptive removal of phosphates in water - Ortiz, Karl Andre (Philippine Journal of Science, 2024)
Mussel shells improperly discarded pose human health and environmental hazards. The present work demonstrates an environmentally friendly method of producing calcium hydroxide nano-plate (CHNP) adsorbent from discarded green mussel shells. The solvents and synthesis conditions herein were carefully chosen to eliminate the generation of hazardous waste, and the process was simplified to minimize energy consumption for producing a potentially commercially viable product. The physical and chemical properties of the synthesized CHNP were characterized using FTIR (Fourier transform infrared), XRD (X-ray diffraction), and SEM (scanning electron microscopy). Batch equilibrium studies in distilled water and simulated seawater revealed that the average maximum adsorption capacity calculated using the Langmuir model was 610 and 653 mg PO43–/g, respectively, and the process followed pseudo-second-order kinetics. These performance values are competitive with similar adsorbents derived from other bivalve shells and with those that are commercially available. The innovative process developed in this work provides the groundwork for producing effective and sustainable phosphorus adsorbents that support economic growth through sustainable consumption of resources, promote energy efficiency, protect biodiversity, use renewable energy sources, and promote a blue circular economy.